Colloquia Germanica Stetinensia - Uniwersytet Szczeciński (Zeszyty naukowe (Uniwersytet Szczeciński), 1988)
German literature and linguistics, but also in the field of cultural and translation studies or glottodidactics (FLT) with reference to German studies, as well as conference reports and short presentations of books.
Keywords: German philology : Periodicals; German language : Periodicals; Philology : Periodicals; German language; German philology; Philology